Pembangunan dan penilaian modul penulisan karangan Bahasa Melayu Tingkatan Empat / Lai Lee Chung - Lai, Lee Chung (2017)
The research purpose is to develop and evaluate the Malay Language essay writing module for form four based on critical thinking, creative thinking and collaborative learning approach. ADDIE model that includes needs analysis, design, development, implementation, and evaluation is the backbone of this study. Needs analysis in phase 1 consists of interviews with ten teachers who are teaching form four Malay Language from three schools and survey on three hundred and twenty five form four students from two schools. Delphi Technique through interview and survey with ten experts panel, who are the lecturers from three local universities, had been implemented in the pre-designed and pre-development phases. The objective is to obtain the opinions of the experts panel on the needs analysis. Delphi Technique which involves expert panels’ input in Phase 2: Design and Phase 3: Development is also used to collect the required data related to pedagogy, content and teaching materials to be incorporated in the essay writing module. In Phase 4: Implementation, the developed module had been used by sixty form four students. The respondents were selected based on purposive sampling who score average and above in Malay Language. Phase 5: Evaluation in this study includes formative evaluation and summative evaluation. For formative evaluation, six form four Malay Language teachers were appointed as panel of assessors to evaluate the strengths and weaknesses of the developed module prior to implementation. From the interview, opinions and suggestions from the panel of assessors were collected to further improve the developed module. Kirkpatrick Evaluation Model which comprised of four levels of evaluation, namely reaction, learning, behaviour and the results has been applied in the summative evaluation. The purpose of the summative evaluation is to evaluate the usability of the modules based on retrospective responder. A pre-test on essay writing and the survey about the behavioural evaluation were carried out before the module was implemented. A post-test on essay writing and survey on the reaction, learning, behaviour and the results were carried out after the module was implemented. Interview with the respondents and reflections written by the respondents about the advantages, disadvantages, problems encountered in using the module, as well as recommendations for improvement in each essay writing module were also analysed in the formative evaluation. The findings showed that the Malay language essay writing module which had been successfully developed based on critical thinking, creative thinking and collaborative learning approach receives positive and encouraging response from the respondents. The developed essay writing module has attracted students’ interest in the essay writing, improved their writing skills, critical thinking skills and creative thinking skill. In addition, students were able to interact with their peers, exchange ideas or opinions, share knowledge, experience and information, solve problems, and receive helps from peers during essay writing assignments through collaborative learning. Finally, it is suggested that teachers, students, and interested parties could make use of this module as a source or reference in the teaching and learning of Malay language essay writing.